Development of Service Mail Management Information System as a Supporting System for Calculating Recapitulation of Remuneration Performance Points at Universitas Negeri Makassar - Al Imran; Haripuddin Haripuddin; Sanatang Sanatang; Muhammad Hasan Z (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This research is research and development (R&D) which aims to produce an official letter management information system, a supporting system for calculating remuneration performance point recapitulation at Makassar State University. Application testing uses ISO/IEC 25010. This study uses the Waterfall development model consisting of five work steps, namely analyzing needs, conducting design, coding, testing and maintenance. The developed system is validated by two system experts, and two content or material experts. The data were collected using questionnaires, interviews and documentation as supporting data for the development of information systems. Data processing uses qualitative and quantitative descriptive analysis techniques. The test results prove that the official letter management information system that has been built meets ISO/IEC 25010 testing standards with the results of testing the functionality suitability aspect in the very decent category. Aspects of performance efficiency with good criteria, aspects of usability with very good category, security aspects obtained level 1 security is at low level criteria with sufficient information. Achievements in the reliability aspect have met Telcordia's testing standards. The maintainability aspect has met three Land testing standards. The compatibility aspect is very feasible and the portability aspect is in the very good category.